Membrane processing effect of blackberry (Rubus adenotrichos) on cytotoxic and pro-apoptotic activities against cancer cell lines - Madrigal Gamboa, Verónica (2021)
Berries are considered an important source of bioactive compounds. In the tropics, Rubus adenotrichos is commonly cultivated, and it is consumed mostly in processed forms. This study assessed the effect of industrial processing in the polyphenol composition and cytotoxic activity against cancer cell lines of four samples of blackberry: fruit, pulp, microfiltered juice, and diafiltered juice. The juice samples showed differences in phenolic concentrations compared with the fruit samples; whereas anthocyanins undergo a 30% to 32% decrease in concentration, the ellagitannins decreased a 93% to 95%. The cytotoxicity assays were performed in stomach (AGS), colon (SW-620), liver (HepG2), and skin (SK-Mel-28) cancer cell lines, and only the fruit and pulp polyphenols achieved IC50 below 200 μg/ml. The IC50 values for the juice samples were over 300 μg/ml. Besides, the pro-apoptotic activity of the fruit polyphenols was assessed and up to 41% of the cells showed early apoptosis with phenolic treatments between 84 to 211 μg/ml.